2016
DOI: 10.1177/0033688216649085
|View full text |Cite
|
Sign up to set email alerts
|

Doodling the Nerves: Surfacing Language Anxiety Experiences in an English Language Classroom

Abstract: This qualitative study explored the use of doodling to surface experiences in the psychological phenomenon of language anxiety in an English classroom. It treated the doodles of 192 freshmen from a premier university in Northern Luzon, Philippines. Further, it made use of phenomenological reduction in analysing the data gathered. Findings reveal that doodling can be an effective tool in surfacing experiences of a psychological phenomena, such as language anxiety, although this may not be generalizable. The gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…The analysis of the FLCAS data indicated that there was no significant difference between doodlers and non-doodlers in terms of their foreign language levels. Although previous research (e.g., de Guzman et al, 2008;Siagto-Wakat, 2016) showed doodling as a working strategy to unveil the internal feelings and attitudes towards an external subject, the present study did not substantiate the anxiety-reducing feature of doodling. The results of the current study revealed that doodling could not significantly reduce the foreign language anxiety learners experienced in the EFL class.…”
Section: International Journal Of Research Studies In Educationcontrasting
confidence: 99%
See 1 more Smart Citation
“…The analysis of the FLCAS data indicated that there was no significant difference between doodlers and non-doodlers in terms of their foreign language levels. Although previous research (e.g., de Guzman et al, 2008;Siagto-Wakat, 2016) showed doodling as a working strategy to unveil the internal feelings and attitudes towards an external subject, the present study did not substantiate the anxiety-reducing feature of doodling. The results of the current study revealed that doodling could not significantly reduce the foreign language anxiety learners experienced in the EFL class.…”
Section: International Journal Of Research Studies In Educationcontrasting
confidence: 99%
“…Doherty (2005) states that doodling is an activity which can decrease the amount of stress in foreign language classroom experienced by L2 learners. The qualitative study conducted by Siagto-Wakat (2016) shows that doodling could be used as an anxiety-reducing activity for university students in an EFL context. The participants utilized doodling as a nonverbal tool to pour their anxiety into unconscious phases, as well as implicitly depicting their anxiety sources.…”
Section: International Journal Of Research Studies In Educationmentioning
confidence: 99%
“…Subsequently, a test was devised and implemented for doodling [32] and a Lancet study published concerning doodling [ 33 ]. Since then, the number of studies of doodling has increased [34,35,36,37,38,39,40] and, in 2015, the 2009 test was replicated [41]. Nevertheless, in over eighty years, this is the extent of peer-reviewed studies on doodling and none of these publications had considered doodling as a valid measure of any internal state until the report on the Health Narratives Research Group from last year [19].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current literature, throughout the world several studies are conducted on strategies that eliminate foreign language anxiety among EFL/ESL learners. The most common ones are: communication, test anxiety, and fear of negative evaluation, classroom activities classroom activities, friendly atmosphere of the classroom, cooperative learning, clear instruction, pace of speech from teachers, self-concept of competence, teachers' behavior, classroom management, Learner's autonym, Identify anxious leaners, uses of technology in the classroom (Abdurahman et al, 2018;Aida, 1994;Alcala, 2002;Anandari, 2015;Atifnigar, Zaheer, et al, 2020;Atifnigar et al, 2021Atifnigar et al, , 2022Brown, 2000;Cinkara, 2016;Fuller, 1978;Grant et al, 2014;Hashemi, 2011;Horwitz et al, 1986;Ismail, 2016;Johnson, 2006;Mejias et al, 1991;Nagahashi, 2007;Otieno et al, 2016;Pappamihiel, 2002;Paradowski et al, 2015;Ratanasiripong et al, 2010;Saunders & Crookall, 1985;Shams, 2005;Siagto-Wakat, 2017;Tanveer, 2007;Tonks et al, 2013;Underwood, 2012;Von Worde, 2003;Walton, 1981;Woodrow, 2006;Young, 1990).…”
Section: Introductionmentioning
confidence: 99%